1989
DOI: 10.1104/pp.91.4.1266
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides in Barley Aleurone Layers and Gibberellic Acid-Induced Changes in Metabolism

Abstract: The plant hormone gibberellin is involved in the regulation ofa number ofdiverse processes, including germination, shoot elongation, and fruit formation. Gibberellin-induced a-amylase synthesis and secretion during germination has been extensively studied and the involvement of Ca2" in this process is well established (4,12,14). However, the molecular mechanism of hormone perception, message transduction, and biochemical regulation is unknown.Membrane-bound phosphoinositides mediate signal transduction across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…The inclusion of authentic standards of 32P-labeled GroPIns3P, GroPIns4P, and GroPIns(4,5)P2 obtained from S. polyrhiza allowed us to confirm an earlier report (Murthy et al, 1989) of the presence of PtdIns4P in barley aleurone cells. We have also revealed the likely presence of PtdIns3P, but at the level of labeling achieved we were unable to confirm the presence of PtdIns(4,5)P2.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…The inclusion of authentic standards of 32P-labeled GroPIns3P, GroPIns4P, and GroPIns(4,5)P2 obtained from S. polyrhiza allowed us to confirm an earlier report (Murthy et al, 1989) of the presence of PtdIns4P in barley aleurone cells. We have also revealed the likely presence of PtdIns3P, but at the level of labeling achieved we were unable to confirm the presence of PtdIns(4,5)P2.…”
Section: Resultssupporting
confidence: 79%
“…We are in agreement with Murthy et al (1989) that the the level of labeling in PtdIns4P is only a small fraction of that achieved in PtdIns. We were unable at the level of labeling achieved to conclusively identify any PtdInsPz species in aleurone tissue.…”
Section: Dlscusslonsupporting
confidence: 91%
See 2 more Smart Citations
“…Murthy and Render [4] showed that phosphoinositides were involved in GAa-induced synthesis and secretion of a-amylase in the aleurone cells of barley seeds. Ladedgenskaya et al [5] showed that GA3 increased activity of Ca 2+-and phospholipid-dependent protein kinase-like enzyme in potato tubers.…”
Section: Introductionmentioning
confidence: 99%